Behavioral inhibition and approach tendencies are associated with striatal activation to loss: Implications for adolescent substance use. (5th November 2022) - Gonçalves, Stefanie F.; Mauro, Kelsey L.; Kinsey-Kerr, Max G.; Fuentes, Alejandro Gamboa; Thompson, James C.; Chaplin, Tara M.
Abstract: Behavioral inhibition/avoidance and approach systems (BIS/BAS), which facilitate avoidance of aversive stimuli and approach of enticing stimuli, are thought to underlie engagement in substance use (SU). However, little is known about the neural correlates of these systems, particularly in adolescence. The current study examined associations between BIS/BAS tendencies and neural response to reward and loss and then examined whether there was an indirect effect of BIS/BAS on later SU initiation through these neural responses. 79 12–14 year olds underwent fMRI at baseline during a card guessing task. Adolescents reported on their BIS/BAS at baseline and on their SU at baseline and through a 3-year follow-up period. Results showed that higher BIS was associated with lower striatal activation and higher BAS with higher striatal activation to monetary loss. BIS and BAS were not associated with neural activation to monetary reward. There was no support that BIS or BAS predicted SU initiation through striatal activation to monetary loss. Overall, these results may suggest that adolescents with the tendency to avoid aversive stimuli assign less salience and adolescents with the tendency to approach enticing stimuli assign more salience to monetary loss. Highlights: Higher BIS was associated with lower striatal activation to monetary loss. Higher BAS was associated with higher striatal activation to monetary loss. BIS and BAS were not associated with neural activation to monetary reward. BIS/BAS did not predict SU initiation through striatal activation to monetary loss.